(untitled) (Medical Forum Monthly, 2024)
Objective: In this study, we intended to measure variation in QT, QTc interval and dispersion before and after hemodialysis in patients of ESRD on MHD. We also tried to check its relationship with various biochemical parameters. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Dialysis centers of SughraShafi Hospital, Narowal and Sir Ganga Ram hospital, Lahore during July 2019. Materials and Methods: Sixty eight patients of ESRD booked for thrice weekly MHD were enrolled in this study. Baseline characteristics of the all patients recorded. Measurement of QT, QTc and QTD are made on 12 leads ECGs during pre and post dialysis period and compared with the values of serum electrolytes and other dialysis related variables recorded at the time of ECG. Results: Male to female ratio was 1.9:1, with mean age of 47 years. QTc and QTD were prolonged in 100% and 53% of patients pre-dialysis and prolonged further among 75% and 66% of patients during post dialysis respectively. Serum potassium, magnesium levels, LVH, and serum bicarbonate appeared to be the main determinants of QTD pre and post dialysis. Conclusion: This study showed that QTcmax and QT dispersion are elevated in hemodialysis patients, and rose further during post-dialysis period. Significant association seen with changes in serum potassium, magnesium, changes in acid-base status and presence of LVH.